Surface Roughness of Glass Ionomer Cements after Application of Different Polishing Techniques - Ante Miličević; Kristina Goršeta; Raimond NV van Duinen; Domagoj Glavina (University of Zagreb. School of Dental Medicine, 2018)
Glass Ionomer Cements (GIC) have been widely used in clinical practice since they have a wide range of positive characteristics: chemical bonding to the tooth surface, fluoride release, a heat-expansion coefficient similar to the tooth, do not require an absolutely dry working area, less volumetric contraction, good color stability. Physical properties can be improved by using external energy such as ultrasound and radiant heat (thermo-curing), which also accelerates chemical curing. Objectives: The aim of this study was to determine the most effective polishing technique and to compare the surface roughness of two Glass Ionomer Cements after treatment with heat (thermo-curing), and without heat treatment during the setting process. Materials and methods: Two polishing systems (Tungsten carbide burs and Sof-Lex discs) were used on two types of GIC (Equia Fil and Ketac Molar Universal). Bluephase 16i LED (Vivadent, Schaan Liechtenstein) light was used for the specimens treated with heat (thermo-curing). Samples without heat treatment are left for 10 minutes to chemically cure. Surface profilometar was used for measuring the mean surface roughness value (Ra). Results: Group with Mylar strip (control group) of each material showed the lowest (Ra) value. The Equia Fil material samples treated with heat (thermo-curing) achieved lower surface roughness values (Ra), and showed lower surface roughness values (Ra) after polishing with a Sof-Lex discs (p<0.05). The results for Ketac Molar Universal samples showed no statistically significant difference (p>0.05) between polishing with Sof-Lex discs and Tungsten carbide burs. Conclusion: Based on the obtained results, it can be concluded that the smoothest surface roughness is achieved by the Mylar strip. Some types of Glass Ionomer Cements can obtain better surface polishing with heat treatment (thermo-curing).